(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
Competition plays a vital role in improving the operational and strategic performance of service enterprises. In a globalized economy, competitive forces drive innovation, quality improvement, and cost efficiency. This paper examines how competition influences efficiency in the service sector through mechanisms such as technological adoption, customer-oriented management, and productivity enhancement. The study also discusses how excessive competition may lead to market failures if not properly regulated. The findings emphasize that sustainable competition fosters innovation, customer satisfaction, and efficient resource utilization, which ultimately improve service quality and profitability.